The Origin Story of India's States - Venkataraghavan Subha Srinivasan (India Penguin Random House India, 2022)
DO YOU KNOW THE STORY OF YOUR STATE? You were born in an Indian state. You went to school in an Indian state. You live and work in an Indian state. You, like every other Indian, call at least one state home. Your state is a big part of your identity. And yet, do you know the story of how your state was created?The Origin Story of India's States is a fascinating and illuminative account of the genesis of India's states. It presents the incredible origin stories of each of India's twenty-eight states and eight union territories, spanning from Independence until today. The state that wasn't even a part of India until 1975; the union territory that had a prime minister for a single day; the state that has not one or two but three capitals; and the union territory that has beaches on both coasts-this book looks into such unique aspects of Indian history and adds to our understanding of how our nation has been built.
Keywords: History Of Countries -- History Of Countries; History Of India -- History Of India